2022
DOI: 10.11591/eei.v11i6.4035
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of augmented reality in video conference based learning during COVID-19 pandemic in higher education

Abstract: Three years after the COVID-19 pandemic emerged, we have adapted to the new normal, especially in the education field. Learning with video conferences has become our daily activity, and learning tools have gotten more prominent attention to gain student engagement, especially in emergency remote teaching (ERT). Since the trends of metaverse campaigns by meta, augmented reality (AR) has increased recognition in education contexts. However, very little research about the acceptance of augmented reality in video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…In contrast, Sunardi et al (2022) demonstrated that hedonic motivation is a significant predictor of behavioral intention in their study, which focused on augmented reality, and participants agreed that the environment was enjoyable and pleasurable. Similarly, Mustafa et al (2022), in their study to determine consumers' usage and acceptance levels of 5G technologies, found that hedonic motivation influenced behavioral intention.…”
Section: Discussion and Con Clus Ionmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, Sunardi et al (2022) demonstrated that hedonic motivation is a significant predictor of behavioral intention in their study, which focused on augmented reality, and participants agreed that the environment was enjoyable and pleasurable. Similarly, Mustafa et al (2022), in their study to determine consumers' usage and acceptance levels of 5G technologies, found that hedonic motivation influenced behavioral intention.…”
Section: Discussion and Con Clus Ionmentioning
confidence: 82%
“…In the study on online theater applications, Aranyossy (2022) Sunardi et al (2022) also found that habit significantly influences behavioral intention in their study. Similarly, Aranyossy (2022), in his study on digital entertainment technologies, found that habit is an important variable that affects both behavioral intention and usage.…”
Section: Discussion and Con Clus Ionmentioning
confidence: 86%
See 1 more Smart Citation
“…Accorriding to Braiki et al [23], the major ICT issues in the education area are inadequate knowledge and practice of ICT in education, lack of reliablity to use the computer in the classroom and lack of practical skills make ICT difficult to use in education. Many universities seek solutions to support teaching and learning activities in preparation for new normal activities after the COVID-19, especially in higher education [24], the implication of this study will be used to consider top-level adminstration in a university that conducts full online/distance learning. Implementation of massive open online course (MOOC) in several countries can be considered.…”
Section: Litreture Reviewmentioning
confidence: 99%
“…Video content, also known as video-based learning [3] has been used in online learning for a long time. The educators create video content as a teaching tool because it able to increase students' knowledge and understanding [4] and improve their study habits [5].…”
Section: Introductionmentioning
confidence: 99%